Optimizing Posterior Condylar Offset and Joint Line Restoration in Revision Total Knee Arthroplasty Using a Contemporary Implant System. Issue 2 (June 2019) - Samson, Anthony J.; Hamilton, David F.; Loh, Brian; MacPherson, Gavin; Burnett, Richard
Abstract : We present a variation of the standard operative technique for the Triathlon total stabilized revision knee system that aims to facilitate recreation of an anatomic joint line, and increase the posterior condylar offset through flexion and posterior translation of the femoral component using short cemented intramedullary stems. We illustrate the technique with a sequential single-surgeon series of 29 patients undergoing total stabilized revision total knee arthroplasty. Joint line ratio is maintained and posterior condylar offset ratio increased from preoperative to postoperatively. Patient reported outcome scores (Oxford Knee Score) significantly improved by 15.6 points at 12 months ( P <0.001) with an overall positive satisfaction outcome of 88%.